The Comparison of Treatment Efficacy and Outcomes of Microneedling and Glycolic Acid Peels for Acne Scar - Quratulain Memon, Sadia Rasheed, Asia Hafeez, Zafar Abbas, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Approximately 9.4% of the global population is affected by the acne. It is one of the most prevalent types of disease around world. Acne scars are produced after a severe attack of acne. Objective: This comparative study was carried out to find the outcomes of two main acne treatments carried out by dermatologist. Study design: It is a randomized and controlled based study conducted at Dermatology department of Liaquat University of Medical and Health Science, Jamshoro and Sir Syed Medical College and Hospital Karachi for the duration of six months from February 2022 to July 2022. Material and Methods: The study comprised of a total of 120 patients, among them there are 49 males and 71 females, divided in three groups. Group 1 contains patients who experienced dermapen microneedling technique. EMLA cream was applied to the face of patients for 40-60 minutes and then microneedling was performed gently. Every 2 weeks microneedling session was carried out and a total of 6 sessions were given to the patients. Results: The patient’s response to the treatment given was also evaluated by using the standard global scar grading system. The three groups reported statistically significant results. Most of the patients reported about improvement in group 1 and 3, however in group 2, 31 patients showed no improvement. Conclusion: The use of microneedling is much more effective than glycolic acid peeling, but if both techniques are used in an alternative manner, it not only gives positive results but also makes skin healthy smooth and shiny. Keywords: Microneedling, glycolic acid chemical peel and acne scars.